LGBTQ+ cardiovascular health equity: a brief review - Bonomo, Jason A.; Luo, Kate; Ramallo, Jorge A. (Frontiers in Cardiovascular Medicine, 2024)
Data shows that social drivers of health (SDOH), including economic stability, racial/cultural identity, and community, have a significant impact on cardiovascular morbidity and mortality. LGBTQ+ (lesbian, gay, bisexual, transgender, queer, and other gender and sexual minority) patients face a variety of unique health risk factors and bear a disproportionate burden of CVD compared to cis-gender, heterosexual peers. There is a paucity of research assessing the etiologies of CVD health disparities within the LGBTQ+ community. Herein, we seek to explore existing literature on LGBTQ+ health disparities with a focus on cardiovascular disease, examine trends impacting LGBTQ+ health equity, and identify strategies and interventions that aim to promote LGBTQ+ cardiovascular health equity on a regional and national level.